Repeated barrier drown-out is required to facilitate long-distance migration of a potamodromous fish - Jason D. Thiem; Benjamin G. Fanson; David Ryan; Gavin L. Butler; David A. Crook; Doug J. Harding; Anthony Townsend; Ian J. Wooden; Ivor Stuart (Aquatic Sciences, 2025)
Migratory fish species are highly vulnerable to stream fragmentation. Potamodromous golden perch ( Macquaria ambigua ) inhabit the barrier-laden Murray–Darling Basin (MDB), Australia’s largest river system, and its lifecycle includes a requirement for uninterrupted stretches of flowing water habitat. Owing to these barriers, large-scale connectivity in many regions is limited to periods of high flow events that facilitate barrier drown-out. We undertook a 3-year (2021–2024) study using telemetry to quantify the movements of 150 adult golden perch from the Barwon–Darling River over a period that encompassed numerous high flow events and flooding. Approximately 75% of tagged golden perch undertook movements > 50 km, with > 90% of movements in an upstream direction, extending up to 1500 km and associated with increased river discharge. Tributary entries were detected on multiple occasions, with an apparent preference for specific tributaries. Ten fish migrated > 1000 km upstream across multiple flow events. The results of this study (1) highlight the importance of the Barwon–Darling River and tributaries as a key migration conduit for adult golden perch, (2) demonstrate that multiple flow events are required to achieve large-scale dispersal and (3) provide quantitative flow-movement relationships that can be used to support inter-regional management actions. These management actions might include barrier removal, the construction of fishways and protection of tributary–mainstem flow events.